ECONOMIC DIPLOMACY AS CHINA’S STRATEGY IN THE ARCTIC REGION TO SUPPORT THE POLAR SILK ROAD INITIATIVE - Agniyah, Nida Nuril; Rahmadan, Yanuar (Journal of Social Politics and Governance (JSPG), 2025)
This study analyzes China's strategic implementation of economic diplomacy in the Arctic region to support the Polar Silk Road (PSR) initiative, an integral part of the Belt and Road Initiative (BRI). Although China is not geographically an Arctic state, it claims the status of a "near-Arctic state" to justify its increasing involvement in Arctic affairs. Utilizing Kishan S. Rana's economic diplomacy framework—consisting of economic salesmanship, networking and advocacy, image building, and regulatory management—this research explores how China promotes infrastructure development, fosters cross-sectoral partnerships, enhances its global image, engages with regulatory frameworks in line with international norms. Furthermore, the study applies the Multi-Track Diplomacy theory to illustrate China's use of multiple diplomatic channels, including government relations, scientific collaboration, business cooperation, and media engagement, to expand its regional influence. Employing a qualitative method and literature-based research, this paper reveals that China's approach is a long-term, multidimensional strategy that combines soft power, economic interests, and institutional participation to gain legitimacy in Arctic governance. Ultimately, China's diplomatic strategy in the Arctic is not merely reactive to global environmental and trade shifts but is part of a broader effort to position itself as a central player in shaping the region's future geopolitical and economic order.